Long-term prognosis of silent cerebral infarction patients - Nobuhara, Kouji; Nishimaru, Katsuya (Japanese Journal of Stroke, 1996)
The purpose of the present study was to evaluate the long-term prognosis of silent cerebral infarciton patients, based on consecutive patients with lacunar lesions detected by cranial CT. Of a series of patients who had undergone CT between 1983 and 1989, 3006 patients without apparent lesions on CT were extracted. Among them, 279 patients who were found to have lacunar lesions and survived for at least 3 months or longer were selected for this study. The subjects were divided into two groups : those with no clinical stroke episodes (silent group), and those with stroke episodes (infarct group). After the clinical profiles of each patient had been investigated, the patients were followed up to assess the prognosis comparatively. Detailed analyses were conducted on 267 patients (follow-up rate, 95.7%) and the mean follow-up period was 57 months. During the follow-up period, stroke occurred in 11 patients (1.73%/year; 9 infarctions and 2 hemorrhages) in the silent group and 16 patients (2.53%/year, 10 infarctions and 6 hemorrhages) in the infarct group. Futhermore, in the silent group, stroke did not occur in the patients (n = 40) who had no risk facotrs, while among the patients (n=80) who did have risk factors, even just one factor, stroke occurred in 10 patients (2.78%/year), which represented approximately the same incidence as in the infarct group. There was no difference between the two groups in the mortality or causes of death during the follow-up period. In conclusion, it can be said that in patients with silent cerebral infarction, stroke occurred less often among patients who had no risk factors and occurred in patients who had any risk factor at approximately the same rate as in patients with symptomatic cerebral infarction.